KUALITAS AIR SUMUR DITINJAU DARI KEBERADAAN Escherichia coli (STUDI KASUS DESA STUNGKIT KECAMATAN BINGAI) - Riwayati Riwayati (Universitas Negeri Medan, 2014)
ABSTRACTThe research is intended to know the existence of Escherichia coli in well-water in Desa Sungkit ,kecamatan Bingai. The research is carried out in November 2013 up to January 2014. The sample is done purposively with the variation of the distance of the stable of the cows with the well, namely I (at home), II (1-5 metres), III (6-10 metres). Of each distance, it is taken 10 homes with three times repetition. The existence of Escherichia coli is analyzed with Most Probable Number (MPN) method. The result of the research show that well-water on the third distance with the stable of the cows show the existence of average of Escherichia coli between 37 colony up to 1093 colony per 100 mL. Kata Kunci : Air sumur, Escherichia coli.